EFEKTIVITAS MACAM AMPAS KOPI TERHADAP STEK “BUNGA PLASTIK” DI DISTRIK KURULU KABUPATEN JAYAWIJAYA: The Effectiveness Of Kinds Of Coffee Dregs Against Cuttings Of "Plastic Flowers" In Kurulu District, Jayawijaya Regency - Mahanani, Anti Uni; Tulak, Alber; Suryani, S.D.A.; Amiruddin Natsir, Akhmad; Nathan Kogoya, Geztha; Bogum, Itera (AgriPeat, 2023)
"Plastic Flower" (Xerochrysum bracteatum) belongs to the Chrysanthemum family. This flower is obtained from the wilderness so it takes effort to develop it. One way to develop it is to apply the provision of organic nutrients sourced from coffee grounds waste. Coffee grounds waste is beneficial for plants to increase their intake of nitrogen, phosphorus and potassium. The aims of the research: 1) to find out the effectiveness of coffee grounds on "Plastic Flower" cuttings; 2) the best type of coffee grounds for growth and cuttings "Plastic Flowers". The research design was a randomized block design consisting of K0 = without coffee grounds (control); K1 = Local coffee grounds, K2 = Kapal Api coffee grounds, K3 = Garuda coffee grounds, K4 = Uang Mas coffee grounds, K5 = Mocca ABC coffee grounds, repeated 5 times. Conclusion: 1) Coffee grounds have a significant effect on the number of shoots aged 4 MST and 6 MST; number of leaves aged 6 MST and 8 MST; live cuttings; rooted cuttings; root length; root fresh weight; The root dry weight of "Bunga Plastik" cuttings and the best type of coffee grounds for the growth and development of cuttings is local Wamena coffee grounds (K4).